MODEL DISCOVERY LEARNING BERBANTUAN GOOGLE MEET UNTUK MENINGKATKAN KEAKTIFAN SISWA MELALUI LESSON STUDY - Yuvita Sekar Taji; Huldiya Syamsiar; Sukariani Sukariani (Universitas Hamzanwadi, 2023)
This study aims to increase student activity in learning Sociology in class XI-9 SMAN 1 Selong. The problem in this study is the low activity of students in learning Sociology in class XI-9 SMAN 1 Selong. The research method uses Classroom Action Research (CAR) with the Discovery Learning model assisted by Google Meet through Lesson Study which consists of three cycles. Data collection tools use 1) Planning (plan); 2) Implementation and Observation (do); 3) Reflection (see). The results showed increased student learning activity in cycle I to cycle III using Google Meet. In the first cycle of the first meeting the results of observations of student activity were still lacking, in the second cycle the first meeting of student activity increased quite a bit. Whereas in cycle III meeting I the activity of students became much increased. Thus it can be concluded that the Google Meet Assisted Discovery Learning Model To Increase Student Activity Through Lesson Study in class XI-9 SMAN 1 Selong.